PENGARUH KETERLIBATAN ORANG TUA TERHADAP KEMANDIRIAN DAN LITERASI ANAK SELAMA MASA PANDEMI - Rosfiani, Okta; Ramadhan, Rizky; Zidni, Zahwa; Achie, Nisbun; Prasetya, Johan Ade; Khiyarannahari, David (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Parental involvement in children's education has long been recognized as a crucial factor influencing children's academic and social development. During the Covid-19 pandemic, many children transitioned to online learning, requiring active parental participation to support their learning processes. This study aims to explore the impact of parental involvement on children's independence and literacy during the pandemic, as well as how such support can foster positive learning habits. This study was conducted in several elementary schools in urban and rural areas, involving 200 parents and their children. Data were collected through surveys and in-depth interviews to understand the level of parental involvement and its impact on children's independence and literacy skills. The primary focus of this research is to identify strategies used by parents to support their children's learning during remote education. The research employed both quantitative and qualitative methods. Quantitative analysis was conducted to measure the relationship between parental involvement levels and children's independence and literacy, while qualitative analysis provided in-depth insights into the experiences of parents and children during the pandemic. Data were analyzed using descriptive and inferential statistical techniques, as well as thematic analysis for qualitative data. The findings indicate that parental involvement significantly enhances children's learning independence and literacy skills. Children who received active support from their parents exhibited higher motivation to learn and better reading abilities compared to those with less support. These results emphasize the importance of parental roles in children's education, particularly in the context of online learning during the pandemic.